Differential Effects of Cr(VI) on the Ultrastructure of Chloroplast and Plasma Membrane of Salvinia minima Growing in Summer and Winter. Relationships With Lipid Peroxidation, Electrolyte Leakage, Photosynthetic Pigments, and Carbohydrates - Prado, Carolina del Valle (2015)
Seasonal variations of chloroplast thylakoids and plasma membrane ultrastructure and changes in some biochemical parameters (e.g., metal accumulation, photosynthetic pigments, carbohydrates, lipid peroxidation, and electrolyte leakage) were studied in fronds of Salvinia minima plants exposed to increasing concentrations of Cr(VI) in both winter and summer. Disorganization of stacked (grana) and unstacked (stroma lamellae) thylakoids was greater in winter chloroplasts than in summer chloroplasts. Plasma membrane was less affected than thylakoids. Photosynthetic pigments, lipid peroxidation, soluble sugars, and starch were affected differently in winter and summer. Our results suggest that much greater ultrastructural alterations and changes in metabolite levels occurring in winter fronds are produced by higher oxidative stress resulting from the interactive effect between low temperature, low solar irradiance, and Cr(VI) toxicity, rather than from metal accumulation per se. Seasonal differences occurring in chloroplast ultrastructure and metabolite concentrations were discussed in relation to metabolic implications. Evaluated parameters represent a relevant approach to enhance knowledge on performance and fitness of plants exposed to heavy metals under fluctuating environmental conditions. This work also indicates that selection of suitable macrophytes to remove Cr(VI) requires an additional analyzing focus on structural and metabolic interactions that occur in plants exposed to heavy metals in contrasting seasons.